Pengaruh Stres Kerja dan Kerjasama Tim Terhadap Turnover Intention di Instalasi Rawat Inap Rumah Sakit Ananda Bekasi - Amalia, Kartika Putri; Nugroho, Sukmo Hadi (Universitas Trunojoyo Madura, 2024)
Turnover intention or the desire to move is the tendency or intention of employees to quit their jobs voluntarily or move from one workplace to another. Burnout is an individual's response to work stress that occurs chronically and develops progressively which causes changes in health that affect work activities. The purpose of this study was to analyze the effect of work stress and teamwork on turnover intention and burnout as an intervening variable. The design of this study is observational analytic which aims to determine the relationship between variables through hypothesis testing, without intervening with the research subjects. The method used in this study is cross-sectional, by collecting data simultaneously at one time. Based on the entire series of analyses, it was found that burnout intervenes with work stress and teamwork on turnover intention so that by reducing work stress and increasing teamwork, burnout will be reduced so that it can reduce the turnover intention rate. Work stress and burnout have an impact on turnover intention, and teamwork has an impact on burnout.